A Concept of Paradi Guna (Samyoga) and its Clinical Utility Monalisa - Hansdah, Monalisa; Das, Arun Kumar; Sahoo, Manoj Kumar; Dash, Bhagya Ranjan (International Research Journal of Ayurveda & Yoga, 2022)
In the present day scenario prime need of Ayurveda is practical applicability of Ayurvedic fundamental principles and research should be more focused on all aspects where scientific inputs should confirm Ayurveda’s principle and philosophy. Ayurveda describes all the substances in terms of five elements, i.e Rasa, Guna, Virya, Vipaka, Prabhav. Among these guna has been accepted as the basic entity of Srushti by Ayurveda as well as Philosophy. Ayurveda has provided significance to all Gunas so that they become useful in clinical practice. Though there are many factors on which accomplishment of treatment depends, among these Charaka has given principle importance of Paradi gunas. Paradi gunas can also be termed as miscellaneous properties which are needed to be present in pharmacists, physicians and researchers. Acharya Charaka says that “Sidhyupaya chikista” i.e successful management of disease is not possible without the knowledge of Paradi Gunas. Paradi gunas play an important role in selection, adaption, manifestation of drug as per condition of the Diseases and the patient, in particular Desha and Kala. Paradi guna are 10 in number. Out of these Samyoga Guna is one of them. No karma can occur without Samyoga. This Samyoga used by physicians and pharmacists in formulating different yogas. One can further understand the importance of Samyoga Guna by using Anupana with Ahara and Aushadha e.g Haritaki churna mixed with Gavya ghrita for Vibandha. Thus the literary review of Paradi Gunas serves to explore the subject of the clinical practice.